The books of Nahum and Zephaniah a study manual - Bennett, T. Miles (Grand rapids, MI Baker, 1968)
Includes bibliographical references.
Keywords: Bible. O.T. Nahum -- commentaries; Bible. O.T. Zephaniah -- commentaries